Economics of climate change in the Arab world - Verner, Dorte; Breisinger, Clemens (World Bank, 2013)
This Economics of Climate Change in the Arab World is presents detailed case studies on the impacts of climate change in the Syrian Arab Republic, Tunisia, and the Republic of Yemen that were summarized. The Arab region is already being impacted by climate change through more frequent cyclones, floods, and prolonged droughts. Thousands of rural producers have seen their crops and herds devastated by extreme conditions, and have been forced to abandon their traditional way of life and migrate to crowded urban areas. Those who stay behind in rural areas struggle to cope with shortages of food and water. Climate change affects countries' economies and households through a variety of channels. Rising temperatures and changes in rainfall patterns affect agricultural yields of both rainfed and irrigated crops, and thus global and local food markets. Adaptation is a process that will take place over decades as new information makes policy makers reevaluate their climate vulnerabilities. Still, by seizing the opportunity to act now and act together, the Arab region can not only meet the immense challenges of climate change but advance the development of its entire people.